Novel perspectives of sodium handling in type 2 diabetes mellitus. Issue 4 (4th July 2022) - Hanson, Petra; Arkill, Kenton P; Merry, Catherine LR; Hussain, Mohammed S; Meersmann, Thomas; Randeva, Harpal S; Pavlovskaya, Galina E; O'Hare, Paul; Barber, Thomas M
ABSTRACT: Introduction: As a key regulator of body water, sodium homeostasis forms an essential component of human physiology. Type 2 Diabetes Mellitus (T2D)-associated sodium overload stems from chronic renal retention of sodium, contributing toward the development of adverse cardiovascular sequelae. Areas covered: Our traditional model of sodium regulation invokes two compartments: extracellular fluid (ECF [plasma and interstitial fluid]) and intracellular fluid (ICF). Data from the Mars program reveal inconsistencies with this two-space model, including mismatches between net body sodium and water. Recent data utilizing 23 Na magnetic resonance imaging (MRI) show a preponderance of bound sodium within human dermis, consistent with a third space repository and providing compelling evidence to support a three-space model in which dermal sodium binding facilitates sodium homeostasis within the ECF and ICF. This buffer is impaired in T2D, with diminishment of dermal bound sodium that may promote deleterious sequelae of sodium overload within the ECF and ICF. Expert opinion: Future studies should focus on novel therapeutic opportunities for sodium regulation in T2D and other conditions of sodium dysregulation. The ratio of free:bound dermal sodium (reflecting sodium storage capacity) could be utilized as a clinical biomarker for salt and water balance, to improve diagnostic accuracy and facilitate clinical decision-making.